BERBAGAI FAKTOR MEMPENGARUHI PEDAGANG ECERAN DALAM PENGAMBILAN KREDIT BANK BRI ( Di Kecamatan Padamara Kab. Purbalingga Prov. Jawa Tengah) - Hari Walujo Sedjati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
Development sell retail in Padamara subdistrict; Purbalingga district; Central Java Province, many kind problem to get credit Bri Bank , depend the collateral for the loan is his owner valuable goods. So that the sell retail pure can’t development and get credit bank no ambition to rise in rank on business development . All of them low need for achievement, on the other hand the sell retaill rich have valuable goods get credit bank have alot of money to capital business increase rank development. The sell retail rich inovativeness the degree to which and individual is earlier than others in his social system to adopt new ideas, became superior ability and good luck . Public policy no take side pure sell retail, so that they are fatalism is degree to which an individual perceives a lack of ability to control his future, which are a belief in limited opportunities for improvement of condition unlucky moment, so can‘t go up on poverty line. Key words : Sell retail, credit, capital and developmen.